Peningkatan Hasil Belajar Siswa melalui Model Kooperatif Tipe TGT dalam Pembelajaran Matematika di Kelas XI - Auliya, Anisa Rima; Ardelia, Nadia Rizki; Usodo, Budi (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – Several phenomena have been observed, including a notable lack of active student engagement, which has led to poor learning outcomes. Consequently, this research aims to investigate the enhancement of student learning outcomes through the implementation of the TGT (Teams-Games-Tournaments) cooperative learning model in eleventh-grade mathematics education.Method – The research method employed is Classroom Action Research (CAR), which comprises two cycles, each encompassing four stages: planning, action, observation, and reflection. The research instrument consists of test questions designed in accordance with the learning objectives. The success indicator for this research is that 75% of the students achieve learning mastery.Findings – The integration of the TGT (Teams-Games-Tournaments) cooperative learning model can improve student learning outcomes. Based on the research results and data analysis in cycle 1, the percentage of students achieving learning completeness was 42%. Since this did not meet the success indicators, the research continued into cycle 2, where an increase of 36% was observed. The percentage of students achieving learning completeness in cycle 2 was 78%, thereby meeting the success indicators, and thus, the research concluded at cycle 2. Research Implications – The implications of this research highlight the importance of selecting a learning model that promotes active student participation in the learning process to enhance students' learning outcomes in vector material. However, a limitation of this research is the restricted sample size, as it focuses solely on one school.